#TITLE_ALTERNATIVE# - JAILANI (NIM 95003210), M.
Way Laay is one of the great rivers in West Lampung Regency, Province of Lampung with river elementary slope equal to 0,014. Because of its slope, if rain falls at once in this catchment’s area, it will be floods. Floods were generally happened during the month of October-April every year. Floods which happened in 2002 suffusing Penggawa Ulu until Laay village, District of Karya Penggawa in West Lampung Regency with river water level reach 0,535 meter above the left side embankment elevation at P.30 Penggawa Ulu village. When floods were subsided, the sloping riverbanks which transporting sand sediment and block so that the longitudinal section will be change become more wide and shallow. This study intention is to know floods discharge from some method calculation of design discharge, either directly from the maximum daily rainfall data or also pursuant to daily discharge calculation result from daily debit from hydrologic coefficient calibrating of side catchment’s area. While its purpose is to get floods discharge value according to the condition of River Way Laay and discharge curve equation which can be used for the calculation of measurement discharge and also as decision making of this river management consideration. The method which used in discharge floods directly calculation from rainfall data is Rational and Snyder Hydrograph Method. While Thornthwaite Method is used to calculate calibration of hydrologic coefficient and daily discharge taken by annual maximum daily discharge for the floods discharge calculation of Gumbel and Log Pearson III Method. This floods discharge calculation result from those methods are compared with river longitudinal section area so that can be known which methods are more compatible to the River Way Laay condition and from those river longitudinal section also got the discharge curve equation which can be used in discharge calculation. The result obtained from this study is Hydrologic Coefficient from side catchments area is not compatible applied at River Way Laay because rainfall data at this catchments area is not homogeneous. While the compatible ones which used as design discharge is Rational and Snyder hydrograph method with both of mean discharge equal to 410.14 m3 / second for the fifth year time return, 481.72 m3/second for tenth year time return, 550.38 m3/second for 20th year time return, 639.25 m3 / second for 50th year time return and equal to 705.85 m3 / second for the 100th year time return, because it is nearest to the river bank full capacities at floods location that is 747.42 m3 / second at P.18 Laay village, 829.37 m3 / second at P.25 between Laay and Penggawa Ulu village border and 937.48 m3 / second at P.30 Penggawa Ulu village. The other result is discharge curve equation of River Way Laay on downstream Q = 34.119 y 2.0721 at P.18 in Laay Village, on middle shares Q = 41.334 y 1.9842 at P.25 between Laay and Penggawa Ulu village and on upstream shares Q= 114.06 y 1.9287 at P.30 in Penggawa Ulu village. While discharge which happened in 2002 is design discharge with time return above 100th year that is 1.310.43 m3 / second which bigger than that is obtained from Rational and Snyder hydrograph method that is 705.85 m3 / second. While from result of river morphology, Way Laay is pertained young river because downstream width estuary) much more small from upstream so that the condition of river hydrolyze can still changed to look for the natural condition which more stable. The suggestion which expected from this study is review study concerning floods discharge in order to compatible with the River Way Laay condition that is doing direct river discharge measurement at this study location and calculate the discharge curve equation at another location for the river longitudinal section from upstream to downstream which is more and detail.